2
$\begingroup$

Disclaimer: It's hard to state this question concisely, so don't confuse it with simpler selections questions. OTOH, I'm sure it's been asked, I just can't find it because I can't guess how someone else would phrase it.

Question:

Suppose I have a palette of $s$ distinct colors and have $m$ people independently choose their favorite $d$ colors from that set.

  • How many ways are there for them to choose $n$ or fewer distinct colors across their selections?
  • Is their a short name (or description) for this kind of selection / problem?

Motivation:

This is interesting because if 100 people chose their top 5 colors from a palette of 34 colors, it would be pretty surprising if they only came up with 6 distinct colors and as a group "neglected" the other 28. I am using this to determine a one-sided p-value for them having $n$ or fewer (i.e. very similar) selections.

Clarifications:

  • Each person chooses $d$ distinct colors (so each samples without replacement).
  • However, all the colors are available to everyone, so different people can include some or all the same colors in their selections.

My solution so far:

Lower Bound: $${{n \choose d}^m}$$ Upper Bound: $${s \choose n}{{n \choose d}^m}$$

The exact answer is in between these.

$\endgroup$
2
  • 1
    $\begingroup$ Welcome to MSE. It is in your best interest that you use MathJax. $\endgroup$ Jun 9, 2018 at 13:41
  • $\begingroup$ Thanks, @JoséCarlosSantos. When I get enough reputation, I'll vote you up. :) $\endgroup$ Jun 9, 2018 at 15:58

1 Answer 1

1
$\begingroup$

The question of getting exactly $n$ different colors points us to generalized Stirling numbers and hence may be computed by inclusion-exclusion the same as ordinary Stirling numbers. Supposing that we have chosen the $n$ colors from the $s$ available ones we classify choices according to the number $q$ of colors that are missing and obtain by PIE

$${s\choose n} \sum_{q=0}^n {n\choose q} (-1)^q {n-q\choose d}^m.$$

This yields for the probability of at most $n$ colors appearing

$$\bbox[5px,border:2px solid #00A000]{ {s\choose d}^{-m} \sum_{p=1}^n {s\choose p} \sum_{q=0}^p {p\choose q} (-1)^q {p-q\choose d}^m.}$$

I verified this formula using the Maple code included below.

with(combinat);

ENUM :=
proc(s, d, m, n)
option remember;
local src, res, part, psize, mset,
    admit, recurse;

    src := choose({seq(q, q=1..s)}, d);

    admit := [seq(0,  q=1..m)];

    recurse :=
    proc(sofar, srcpos, count, incl)
    local seen;

        if incl then
            admit[count] := admit[count] + 1;
        fi;

        if srcpos > nops(src) or count = m then
            return;
        fi;

        recurse(sofar, srcpos+1, count, false);

        seen := sofar union src[srcpos];
        if nops(seen) <= n then
            recurse(seen, srcpos+1, count+1, true);
        fi;
    end;

    recurse({}, 1, 0, false);

    res := 0;

    part := firstpart(m);

    while type(part, `list`) do
        psize := nops(part);
        mset := convert(part, `multiset`);

        res := res + admit[psize] *
        m!/mul(p!, p in part) *
        psize!/mul(p[2]!, p in mset);

        part := nextpart(part);
    od;

    res*binomial(s,d)^(-m);
end;


X :=
(s, d, m, n) ->
binomial(s,d)^(-m) *
add(binomial(s,p) *
    add(binomial(p,q)*(-1)^q*binomial(p-q,d)^m,
        q=0..p), p=1..n);

Addendum. We should get probability one when we have $n=s.$ To prove this we write

$${s\choose d}^{-m} \sum_{p=0}^s {s\choose p} \sum_{q=0}^p {p\choose q} (-1)^{p-q} {q\choose d}^m \\ = {s\choose d}^{-m} \sum_{q=0}^s {q\choose d}^m (-1)^q \sum_{p=q}^s {s\choose p} {p\choose q} (-1)^{p}.$$

Observe that

$${s\choose p} {p\choose q} = \frac{s!}{(s-p)! \times q! \times (p-q)!} = {s\choose q} {s-q\choose s-p}$$

so this is

$${s\choose d}^{-m} \sum_{q=0}^s {q\choose d}^m (-1)^q {s\choose q} \sum_{p=q}^s {s-q\choose s-p} (-1)^{p} \\ = {s\choose d}^{-m} \sum_{q=0}^s {q\choose d}^m (-1)^q {s\choose q} \sum_{p=0}^{s-q} {s-q\choose s-q-p} (-1)^{p+q} \\ = {s\choose d}^{-m} \sum_{q=0}^s {q\choose d}^m {s\choose q} \sum_{p=0}^{s-q} {s-q\choose p} (-1)^p.$$

Evaluating the inner sum we now find

$${s\choose d}^{-m} \sum_{q=0}^s {q\choose d}^m {s\choose q} \times [[q=s]] = {s\choose d}^{-m} {s\choose d}^m {s\choose s} = 1$$

and the sanity check goes through.

Remark. The details of the Stirling number argument are in the comments to MSE 2791477.

$\endgroup$

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .